Effect of Freeze-Drying on the Engineering, Cooking, and Functional Properties of Chickpea Cultivars Grown in an Indian Temperate Climate - Najeebah Farooq; Idrees Ahmed Wani (Foods)
The present study investigates the impact of freeze drying on the physical, cooking, and functional properties of some chickpea (Cicer arietinum) cultivars. Freeze drying was applied to reduce the cooking time in addition to evaluating its effect on other quality attributes. The results revealed a significant reduction in cooking time in the freeze-dried chickpeas (67.00–77.33 min) compared to the control chickpeas (80.33–93.66). Additionally, functional properties were enhanced, such as the water absorption capacity, which increased from 0.84–0.98 g/g to 1.051–1.24 g/g, the oil absorption capacity, which increased from 0.73–0.98 g/g to 0.909–980 g/g, and the foaming capacity, which increased from 42.58–45.16% to 44.37–47.20%. The textural analysis revealed that freeze drying resulted in a decrease in hardness from 2.72–3.91 kg to 1.48–2.05 kg among the cultivars. The structural analysis indicated notable modifications in starch granules, supporting the observed changes in pasting behavior, which exhibited increased peak and breakdown viscosities. However, a reduction in antioxidant activity, viz., DPPH, TPC, TFC, and FRAP, was observed, indicating a potential trade-off between the preservation technique and nutritional quality. This study underscores the potential of freeze drying to improve the cooking and functional properties of chickpeas, with a special focus on their cooking properties.